PENGARUH NAUNGAN KAYU KUKU ( PERICORPSIS MOONIANA THW) TERHADAP PERTUMBUHAN DAN BIOMASSA NILAM (POGESTEMON CABLIN BENTH) PADA SISTEM AGROFORESTRY DI KABUPATEN KOLAKA SULAWESI TENGGARA - Sabaruddin Sabaruddin; Syamsuddin Millang; Budirman Bachtiar; Andi Khairil A.Samsu (Program Studi Kehutanan Universitas Muslim Maros, 2020)
The results of the non-timber forest have become an excellent for the farmers to increase their economy. One of these non-timber forests is essential oil. There are several types of essential oil-producing plants of a patchouli plant. The existence of patchouli plants in the region of Kolaka today proved to be able to answer the economic problem of Community. The research is examined about the effect of nail wood to the growth and biomass of patchouli plants (pogestemon cablin Benth). The treatment of This research is the comparison of the nail wood shade (pericorpsis mooniana TW) Less (5-7 trees nails/plot), very less (9-11 tree Nails/plot), and without shade as a control. The results of the study showed that the stunted plants have increased crop height growth, while the treatment without shade gives the growth of the largest number of leaves and biomass.